Chest wall injuries due to cardiopulmonary resuscitation and the effect on in-hospital outcomes in survivors of out-of-hospital cardiac arrest. Issue 6 (December 2021) - Prins, Jonne T.H.; Van Lieshout, Esther M.M.; Van Wijck, Suzanne F.M.; Scholte, Niels T.B.; Den Uil, Corstiaan A.; Vermeulen, Jefrey; Verhofstad, Michael H.J.; Wijffels, Mathieu M.E.
Abstract : BACKGROUND: This study aimed to assess the prevalence of chest wall injuries due to cardiopulmonary resuscitation for out-of-hospital cardiac arrest (OHCA) and to compare in-hospital outcomes in patients with versus without chest wall injuries. METHODS: A retrospective cohort study of all intensive care unit (ICU)–admitted patients who underwent cardiopulmonary resuscitation for OHCA between January 1, 2007, and December 2019 was performed. The primary outcome was the occurrence of chest wall injuries, as diagnosed on chest computed tomography. Chest wall injury characteristics such as rib fracture location, type, and dislocation were collected. Secondary outcomes were in-hospital outcomes and subgroup analysis of patients with good neurological recovery to identify those who could possibly benefit from the surgical stabilization of rib fractures. RESULTS: Three hundred forty-four patients were included, of which 291 (85%) sustained chest wall injury. Patients with chest wall injury had a median of 8 fractured ribs (P25 –P75, 4–10 ribs), which were most often undisplaced (on chest computed tomography) (n = 1, 574 [72.1%]), simple (n = 1, 948 [89.2%]), and anterior (n = 1, 785 [77.6%]) rib fractures of ribs 2 to 7. Eight patients (2.3%) had a flail segment, and 136 patients (39.5%) had an anterior flail segment. Patients with chest wall injury had fewer ventilator-free days (0 days [P25 –P75, 0–16 days] vs. 13 days [P25 –P75, 2–22 days]; p = 0.006) and a higher mortality rate (n = 102 [54.0%] vs. n = 8 [22.2%]; p < 0.001) than those without chest wall injury. For the subgroup of patients with good neurological recovery, the presence of six or more rib fractures or a single displaced rib fracture was associated with longer hospital and ICU length of stay, respectively. CONCLUSION: Cardiopulmonary resuscitation–related chest wall injuries in survivors of OHCA and especially rib fractures are common. Patients with chest wall injury had fewer ventilator-free days and a higher mortality rate. Patients with good neurological recovery might represent a subgroup of patients who could benefit from surgical stabilization of rib fractures. LEVEL OF EVIDENCE: Therapeutic, level IV; Epidemiological, Level IV. Abstract : Supplemental digital content is available in the text.